ANALISA FAKTOR YANG MEMPENGARUHI MINAT NASABAH MENGGUNAKAN INTERNET BANKING Studi Empiris : Nasabah Bank BRI Cabang Bengkulu - , HARTANTYO HADHI NUGROHO; , Syaiful Ali, S.E., M.I.S., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed to test and analyze the model of clientsâ willingness to try the internet banking service covering some concepts, which are trust, attraction, and clientsâ commitment. This research also analyzes the factors influencing the clientsâ trust and commitment in using the internet banking service. In the model of internet banking service covering the trust concept, it is influenced by several factors, which are security, regulatory control, technology advancement, and reputation. Besides, the clientsâ commitment in the internet banking model involves the affective and calculative commitment which is influenced by the attraction factor. This research is located at Bank Rakyat Indonesia, Bengkulu Branch. The data gathered in this research are analyzed by using the Structural Equation Model (SEM) which employs AMOS 19 application. The respondents of this research are the clients of Bank Rakyat Indonesia Bengkulu Branch which consist of 197 respondents. The results of this research show that (1) the security, technology advancement, and reputation variables possess positive influences towards the trust of the clients to the internet banking service, (2) the trust variable possesses positive influences towards the willingness of the clients in using the internet banking service, (3) the attraction variable possesses positive influences towards the clientsâ affective and calculative commitment in using the internet banking service, and (4) the affective commitment possesses positive influences towards the willingness of the clients in using the internet service banking.